Challenges of Management System in Temporary Accommodation after Natural Disasters in Iran From Gilan-Zanjan Earthquake (1990) to Kermanshah Earthquake (2017) - Mahsa Bashiri; Mohammadreza Bemanian (مسکن و محیط روستا)
Many countries in the world have experienced different sorts of disasters and consequently have suffered large losses of life and property. After disasters, there are three possible scenarios: in the first scenario, available (current) accommodation is not ruined, as a result no gap will be created; the second scenario declares that the current housing is ruined and the available gap will be filled by reconstruction of permanent housing, and the last scenario states that the current housing is ruined and the available gap will be filled by temporary shelters till the construction of permanent housings are fulfilled. Our country always has been exposed to different natural disasters. Temporary housing, in some disasters, has been considered as a separate stage in the reconstruction procedures based on the extent of damage, climatic conditions and duration of reconstruction period. Therefore, management of providing accommodation has been regarded as a prominent phase in post-disaster situations. In our country, providing accommodation after disasters has been described in three steps: The first step, providing emergency shelter, is the responsibility of the Red Crescent Society, the second stage, providing permanent housing, is specifically the duty of Housing Foundation and the last step is temporary housing. Although temporary housing has been considered as a step in the procedure of reconstruction for displaced people, regarding the resumption of normal life till the time of permanent housing construction, previous experiences declare that temporary housing has been underestimated as the link between emergency and permanent housing. While the crucial role of temporary housing in the procedure of affected residents’ recovery of normal life is so obvious, no definite operator, structure and procedure have been specified so far. This research has been led examining the previous temporary housing experiences in Iran aiming identification of the managerial and governmental gaps of emergency and permanent shelters. As the case study, data and documentations of temporary housing of 1990 Guilan-Zanjan, 2003 Bam, 2012 East Azerbaijan and 2017 Kermanshah earthquakes have been compiled. The data gathering procedure was accomplished in three phases: (1) studying documents and data in archives and libraries and the operations related to temporary housing; (2) Interviews with well-informed managers of the field; (3) in-field observation of the last two earthquakes. Temporary housing type, locating, preparing the infrastructures, delivering the built temporary units, maintenance and management of leaving the temporary housing have been covered here in this study. According to the performed research, the most prominent challenge in the temporary housing procedure in Iran is the lack of concrete definition of the term which results in unclear locating of temporary hosuing in the procedure of reconstruction, the lack of regulatory governing systems and lack of precise planning in a manner that not only there is no clear plans for providing homes in transition period, but also the role of different organizations are not clearly defined and responsibilities are decided based on the occurred situation. The lack of definition ends with chaos, lack of specified scope of responsibilities of each organization in temporary housing as well as lack of coordination between different organizations. Sometimes, items of importance are neglected like maintenance of temporary housing and providing washrooms in transition period.